PEMODELAN BANGKITAN PERGERAKAN (TRIP GENERATION) PADA KAWASAN SEKOLAH TERPADU (STUDI KASUS : JALAN SULTAN SYARIF QASIM, JALAN HANGTUAH, DAN JALAN DR. SUTOMO KOTA PEKANBARU): PEMODELAN BANGKITAN PERGERAKAN (TRIP GENERATION) PADA KAWASAN SEKOLAH TERPADU (STUDI KASUS : JALAN SULTAN SYARIF QASIM, JALAN HANGTUAH, DAN JALAN DR. SUTOMO KOTA PEKANBARU) - Okky Permana (LPPM Universitas Abdurrab, 2023)
The integrated school area is a place prone to traffic jams. The purpose of this study is to create a motion generation model. The method of data analysis and testing is linear regression analysis using a statistical program (JASP). Retrieval of data by counting the number of vehicles that deliver and pick up. Based on the results of calculations and analysis that has been done, the best model chosen for movement generation is Y1 = -44.826 + 0.241 X1 + 1.942 X2 + 7.294 X4 with an RÂ² value of 0.996 and the best model chosen for movement attraction is Y2 = -60.461 + 0.235 X1 + 1.98 X2 + 7.92 X4 with an RÂ² value of 0.995.